High Content Fe(Iii) Electrocatalyst for the Oxygen Reduction and Evolution Reactions. Spectroscopic, Electrochemical, and Theoretical Insights - Zagal-Moya, J; Zagal-Moya, J; Tasca-Gottardo, F; Tasca-Gottardo, F; Zúñiga-Loyola, C; Zúñiga-Loyola, C (Elsevier Ltd, 2025)
X-ray photoelectron spectroscopy (XPS) and X-ray absorption spectroscopy (XAS), DFT simulations, and standard electrochemical methods were used to analyse the high Fe(III) content of the synthetized Fe phthalocyanine (FePc) axially coordinated to 4-amino-3-nitropyridine (NPy). XPS analysis reveals that NPy exerts a high electron-withdrawing power on the Fe centre causing a shift to a more positive value of E0’Fe(III)/(II) contrasted to FePc-CNT with a ΔE0’ = [E0’FePc-NPy-CNT(III)/(II) - E0’FePc-CNT(III)/(II)] = 56 mV, which evidence the possibility to fine-tune this value. XAS and XANES analyses indicate a decreased electron density in the metal centre causing lower interactions with O2. Consecutively, the Fe2+/Fe3+ ratio changes from 0.95 to 0.51 for FePc-CNT and Fe-NPy-CNT, respectively. The electrocatalytic studies of the oxygen reduction reaction (ORR) in alkaline media, show better performances than the commonly used Pt 20% electrocatalyst in terms of overpotential (ΔE0’ = [E0 onset Fe-NPy-CNT - E0 onset Pt0] = 35 mV) and similar TOF rates at 0.9 V vs. RHE (∼1.00 e− site−1 s−1). DFT calculations show that both FePc-Py-CNT and FePc-NPy-CNT catalysts have nearly equal interactions with O2 (−0.37 eV and −0.32 eV, respectively). However, the O2 bond distance in the FePc-NPy-CNT system is 11% greater compared to the FePc-Py-CNT system explaining the superior performance of the FePc-NPy-CNT catalyst for the oxygen reduction reaction (ORR). Additionally, the interaction with H2O is stronger in the -NPy-configuration, which is consistent with the experimental results. © 2024 Hydrogen Energy Publications LLC